Evaluation of outcome in open and stapler haemorrhoidectomy in grade III/IV haemorrhoids - Singh, Manju; Agarwal, Amit; Pandey, Kush (International Surgery Journal, 2020)
Background: Haemorrhoids are one of most common benign anorectal malformation worldwide. There are various surgical treatment modalities for 3rd and 4th degree haemorrhoids. Open haemorrhoidectomy was the most widely practiced and is considered the current gold standard. In search of a newer surgical technique, stapler has been introduced for haemorrhoidectomy and has revolutionised operative procedures over the last decade world-wide due to its ease and simplicity and lesser post-operative complications. The following study was done to evaluate the outcome of open versus stapled haemorrhoidectomy in terms of post-operative pain, postoperative bleeding, duration of surgery, duration of hospital stays in a medical college hospital at Raipur, Chhattisgarh. Methods: This was a prospective follow-up study, in patients undergoing surgery for grade III/IV haemorrhoids conducted in the Department of Surgery, Dr BRAM Hospital, Raipur, from August 2017 to July 2018. Fourteen patients underwent stapled haemorrhoidopexy and eighteen underwent open haemorrhoidectomy. All patients were reviewed immediately after surgery, at discharge and at 1, 3 and 10 weeks post-operatively. The two groups were compared for post-operative outcomes and complications. Results: The majority of patients in the study were males and had grade 4 haemorrhoids. Stapled haemorrhoidopexy group had shorter duration of surgery, less postoperative pain, shorter duration of hospital stays as compared with open haemorrhoidectomy group. There were no major post-operative complications in the follow up period of 10 weeks in the stapled group. Conclusions: Stapled haemorrhoidopexy is a safer alternative to open haemorrhoidectomy with many short-term benefits.